Play therapy with children: the Malaysian context - Nawawi, Junita (Pearson, 2012)
This chapter aims to introduce play therapy as a form of intervention used in children counselling and psychotherapy. Various aspects of the use of play therapy with children are examined, including its application within the Malaysian context as well as the challenges and constraints of its practice in this country. The chapter starts with a brief history of play therapy, followed by an overview of play therapy, which includes a description of the play therapy room, the different tools of play therapy and the play therapy session itself. This is followed by a literature review of the effectiveness of play therapy as an intervention with children, and recent developments in the field of play therapy. It then discusses play therapy in the Malaysian context. The chapter concludes with some recommendations for future research and some suggestions for the growth and advancement of the field, specifically with respect to its practice in Malaysia.